The Impact of Entrepreneurial Education and Motivation on Entrepreneurial Success: Mediating Role of Entrepreneurial Attitude - Hajar Dewantara; Soussou Raharimalala (CV. Sakura Digital Nusantara, 2025)
Unemployment is a major problem in Indonesia. This occurs because Indonesia is a country with a relatively high population growth rate, which affects the competition for job opportunities. One effective way to address the unemployment issue is to create or increase the number of entrepreneurs. This study aims to determine the direct and indirect effects of Entrepreneurial Education, entrepreneurial motivation, and entrepreneurial attitude on entrepreneurial success. This research uses a descriptive explanatory quantitative approach that describes the relationships among variables with a population of 128 students. The sampling technique employed is Proportional Random Sampling, which involves 128 students from the Entrepreneurship Program at Makassar State University. The research results show that both directly and indirectly, entrepreneurial education, entrepreneurial motivation, and entrepreneurial attitude have a significant effect on entrepreneurial success. Based on the results of this study, it can serve as a source of information or a reference for educators or lecturers to guide and mentor students regarding the development of entrepreneurial skills. It is hoped that students will deepen their skills related to business management so that they are not only focused on the products produced but are also capable of marketing activities and making decisions based on business evaluations with the goal of developing the business. Additionally, for future researchers, it is recommended to delve deeper and expand this study in terms of variables and the development of research methods